Do Workers Work More if Wages Are High? Evidence from a Randomized Field Experiment - Fehr, Ernst; Goette, Lorenz (American Economic Review, 2007)
Most previous studies on intertemporal labor supply found very small or insignificant substitution effects. It is possible that these results are due to constraints on workers' labor supply choices. We conducted a field experiment in a setting in which workers were free to choose hours worked and effort per hour. We document a large positive elasticity of overall labor supply and an even larger elasticity of hours, which implies that the elasticity of effort per hour is negative. We examine two candidate models to explain these findings: a modified neoclassical model with preference spillovers across periods, and a model with reference dependent, loss-averse preferences. With the help of a further experiment, we can show that only loss-averse individuals exhibit a negative effort response to the wage increase. (JEL J22, J31)